Effectiveness of Crown Preparation Assessment Software As an Educational Tool in Simulation Clinic: A Pilot Study. Issue 8 (1st August 2016) - Tiu, Janine; Cheng, Enxin; Hung, Tzu-Chiao; Yu, Chuan-Chia; Lin, Tony; Schwass, Don; Al-Amleh, Basil
Abstract : The aim of this pilot study was to evaluate the feasibility of a new tooth preparation assessment software, Preppr, as an educational tool for dental students in achieving optimal parameters for a crown preparation. In February 2015, 30 dental students in their fourth year in a five‐year undergraduate dental curriculum in New Zealand were randomly selected from a pool of volunteers (N=40) out of the total class of 85. The participants were placed into one of three groups of ten students each: Group A, the control group, received only written and pictorial instructions; Group B received tutor evaluation and feedback; and Group C performed self‐directed learning with the aid of Preppr. Each student was asked to prepare an all‐ceramic crown on the lower first molar typodont within three hours and to repeat the exercise three times over the next four weeks. The exercise stipulated a 1 mm finish line dimension and total convergence angles (TOC) between 10 and 20 degrees. Fulfillment of these parameters was taken as an acceptable preparation. The results showed that Group C had the highest percentage of students who achieved minimum finish line dimensions and acceptable TOC angles. Those students also achieved the stipulated requirements earlier than the other groups. This study's findings provide promising data on the feasibility of using Preppr as a self‐directed educational tool for students training to prepare dental crowns.